Lentiviral vectors as tools to understand central nervous system biology in mammalian model organisms - Hughes, Stephanie M.; Parr-Brownlie, Louise C.; Bosch-Bouju, Clementine; Schoderboeck, Lucia; Sizemore, Rachel; Abraham, Wickliffe (Frontiers in Molecular Neuroscience, 2015)
Lentiviruses have been extensively used as gene delivery vectors since the mid-1990’s. Usually derived from the human immunodeficiency virus (HIV) genome, they mediate efficient gene transfer to non-dividing cells, including neurons and glia in the adult mammalian brain. In addition, integration of the recombinant lentiviral construct into the host genome provides permanent expression, including the progeny of dividing neural precursors. In this review, we describe targeted vectors with modified envelope glycoproteins and expression of transgenes under the regulation of cell-selective and inducible promoters. This technology has broad utility to address fundamental questions in neuroscience and we outline how this has been used in rodents and primates. Combining viral tract tracing with immunohistochemistry and confocal or electron microscopy, lentiviral vectors provide a tool to selectively label and trace specific neuronal populations at gross or ultrastructural levels. Additionally, new generation optogenetic technologies can be readily utilized to analyse neuronal circuit and gene functions in the mature mammalian brain. Examples of these applications, limitations of current systems and prospects for future developments to enhance neuroscience knowledge will be reviewed. Finally, we will discuss how these vectors may be translated from gene therapy trials into the clinical setting.